Predictors of non-sentinel lymph node metastasis in clinical early stage (cT1-2cN0) breast cancer patients with 1/2 metastatic sentinel lymph nodes - Lale, Azmi; Yur, Mesut; Ozgul, Halit; Alkurt, Ertugrut Gazi; Yildirim, Nilgun; Aygen, Erhan; Arikan, Turkmen Bahadir (Elsevier Singapore Pte Ltd, 2020)
Objective: The purpose of this study was to determine the risk factors that caused non-sentinel lymph nodes (nonSLNs) metastasis by considering the clinicopathological characteristics of patients who have 1-2 sentinel lymph node (SLN) metastasis in the clinical early stage (T1-2, NO) breast cancer. Methods: The demographic and clinicopathological characteristics of the patients were recorded retrospectively. Among these, age, size of the primary breast tumor, tumor localization and multifocality/multicentricity status, preoperative serum Neutrophil/ Lymphocyte rate (NLR), c-erbB2/HER2-neu status, Estrogen Receptor (ER) and Progesterone Receptor (PR) status, primary tumor proliferation index (Ki-67), histopathological grade, molecular subtypes, histopathological subtypes, nipple/areola infiltration, Lymphatic Invasion (LI), Vascular Invasion (VI), Perineural Invasion (PNI), number of metastatic SLN m(SLN), mSLN diameter, SLN Ex-tranodal Extension (ENE) status, and number of metastatic nonSLNs were recorded. Results: According to the univariate analysis, the HER2 positivity, Ki-67 >=%20, mSLN diameter, LI, VI, PNI, ENE and molecular subtypes were found to be significant. However, the age, tumor localization, multifocality/multicentricity, T stage, ER and PR status, tumor size, histopathological grade and subtypes, nipple/areola infiltration and NLR were not found to be significant. In the multivariate analysis, significant independent predictors in nonSLN metastasis development were found to be HER2 positivity, PNI, mSLN diameter >= 10,5 mm and ENE. Conclusion: The HER2 positivity, ENE, PNI and mSLN diameter >= 10,5 mm were found to be very strong predictors in nonSLN metastasis development. The findings of this study have the potential to be a guideline for surgeons and oncologists when determining their patients' treatment plan. These components are candidates for inclusion among the clinicopathological factors that may be used in the new nomograms due to their higher sensitivity and specificity. (C) 2019 Asian Surgical Association and Taiwan Robotic Surgery Association. Publishing services by Elsevier B.V.
Keywords: Axillary lymph node metastasis; Breast cancer; nonsentinet lymph node; Predictor; Sentinel lymph node